Autocad Application Training for SMK Karya Bakti Gresik in Supporting Independent Learning Program for the Independent Campus (MBKM): Pelatihan Aplikasi Autocad bagi SMK Karya Bakti Gresik dalam Mendukung Merdeka Belajar Kampus Merdeka (MBKM) - Meryanalinda; Sundari, Putri; Ardian, Dedy Rachman (Universitas Muhammadiyah Sidoarjo, 2022)
CAD (Computer Aided Design) is a computer program for drawing a product. The use of CAD can be in the form of 2-dimensional or 3-dimensional drawings. The advantage of using this CAD computer program is to make it easier and faster to create and change a product/component drawing. Besides that, this program is also useful to make it easier to complete image data such as material type, dimensions, number of products and so on. Mastery of the AutoCAD application is very necessary for students and teachers of Vocational High Schools (SMK), especially in the mechanical engineering department of SMK Karya Bhakti Gresik. This is because they have limited facilities and infrastructure in learning AutoCAD. The ability to use AutoCad for vocational students is a provision to enter the world of work after graduating from school, one of which is to work in the industrial world. Where in the era of Industry 4.0, many companies demand AutoCad capabilities as a condition for joining vocational graduates. Based on this, the competence of AutoCad for SMK Karya Bakti Gresik students needs to be improved. One of the learning processes to improve this competency is to provide AutoCAD application training for SMK Karya Bhakti Gresik students. The training method used is a workshop, where students are given material about AutoCad, then practice AutoCAD directly at the Multimedia Laboratory of the University of Gresik. The participants of this training focused on students in grades X and XI of the Mechanical Engineering Department of SMK Karya Bakti with a training duration of 2 days.